Fibrodysplasia ossificans progressiva (stone man syndrome): a case report - Zakir Ali Shah (Journal of Medical Case Reports, 2019)
Abstract Background Fibrodysplasia ossificans progressiva is an ultrarare autosomal dominant disorder and disabling syndrome characterized by postnatal progressive heterotopic ossification of the connective tissue and congenital malformation of the big toes. Fibrodysplasia ossificans progressiva has worldwide prevalence of about 1 in 2 million births. Nearly 90% of patients with fibrodysplasia ossificans progressiva are misdiagnosed and mismanaged and thus undergo unnecessarily interventions. So far, the number of reported existing cases worldwide is about 700. Clinical examination, radiological evaluation, and genetic analysis for mutation of the ACVR1 gene are considered confirmatory tools for early diagnosis of the disease. Association of fibrodysplasia ossificans progressiva with heterotopic ossification is well documented; however, postsurgical exaggerated response has never been reported previously, to the best of our knowledge. Case presentation We report a case of a 10-year-old Pakistani boy brought by his parents to our institution. He had clinical and radiological features of fibrodysplasia ossificans progressive and presented with multiple painful lumps on his back due to hard masses and stiffness of his shoulders, neck, and left hip. He underwent surgical excision of left hip ossification followed by an exaggerated response in ossification with early disability. Radiological examination revealed widespread heterotopic ossification. All of his laboratory blood test results were normal. Conclusion Fibrodysplasia ossificans progressiva is a very rare and disabling disorder that, if misdiagnosed, can lead to unnecessary surgical intervention and disastrous results of early disability. We need to spread knowledge to physicians and patients’ family members about the disease, as well as its features for early diagnosis and how to prevent flare-up of the disease to promote better quality of life in these patients.